Enhanced production of ginsenoside compound K by synergistic conversion of fermentation with Aspergillus tubingensis and commercial cellulase - Lee, Yong-In; Song, Woo-Seok; Oh, Deok-Kun (Frontiers in Bioengineering and Biotechnology, 2025)
Fermentation of ginseng extract is limited by the low concentration of compound K (CK), a bioactive ginsenoside. In this study, a novel approach combining Aspergillus tubingensis fermentation with Aspergillus niger cellulase conversion was used to enhance CK production from high concentrations of American ginseng extract (AGE). The reaction conditions, including the feeding rate and concentrations of carbon source, enzyme type, AGE and enzyme concentrations, temperature, pH, and timing of enzyme addition, were optimized. Under optimized conditions, this combined method achieved an enhanced CK production of 8.06 g/L (13.0 mM) after 168 h, with a productivity of 48 mg/L/h. This approach led to a 2.0-fold increase in concentration and a 1.7-fold increase in productivity when compared with traditional fermentation using the same strain. The findings of this study demonstrate the synergistic effect of combining fermentation with enzyme conversion to improve CK production.